Investigating Teachers' Beliefs in Inclusive Education and Their Levels of Teacher Self-Efficacy: Are Teachers Constrained in Their Capacity to Implement Inclusive Teaching Practices? - Stuart Woodcock; Kathy Gibbs; Elizabeth Hitches; Chloe Regan (MDPI AG, 2023)
Inclusive education caters for all students and embraces their unique characteristics, backgrounds, and abilities. While many challenges persist that prevent inclusion from being fully embraced and implemented, such as varying definitions of what inclusion is at an international, national, and intra-national level, teachers' attitudes towards inclusion and their belief in their capabilities may play an important role. This paper examined the relationship between 208 Australian primary and secondary teachers' beliefs in inclusive education and their levels of teacher self-efficacy using t-tests. The relationship between these factors and teachers' years of teaching experience, age, and qualifications were also investigated. The findings show that teachers who believe inclusive education is an effective way to teach all students reported higher levels of teacher self-efficacy than those who did not. Differences across teacher demographics raised a number of questions, including the role of additional qualifications and the potential influence of social attitudes towards inclusion over time on teachers' own beliefs, each of which warrants investigation. Recommendations from the findings suggest that professional learning which supports teachers to successfully implement inclusive teaching strategies, may assist to bolster their belief in their capabilities in inclusive classrooms and in the effectiveness of inclusive education for all.